Cooling of a periodic heat-generating solid element in an electronic cabinet using a non-Newtonian pseudoplastic nanofluid and a heat-conducting substrate - Loenko, Darya; Öztop, Hakan Fehmi; Sheremet, Mikhail A. (Emerald Group Publishing Ltd, 2023)
PurposeNowadays, the most important challenge in mechanical engineering, power engineering and electronics is a development of effective cooling systems for heat-generating units. Taking into account this challenge, this study aims to deal with computational investigation of thermogravitational energy transport of pseudoplastic nanoliquid in an electronic chamber with a periodic thermally producing unit placed on the bottom heat-conducting wall of finite thickness under an influence of isothermal cooling from vertical side walls. Design/methodology/approachThe control equations formulated using the Boussinesq approach, Ostwald-de Waele power law and single-phase nanofluid model with experimentally based correlations of Guo et al. for nanofluid dynamic viscosity and Jang and Choi for nanofluid thermal conductivity have been worked out by the in-house computational procedure using the finite difference technique. The impact of the Rayleigh number, nanoadditives concentration, frequency of the periodic heat generation from the local element and thickness of the bottom solid substrate on nanoliquid circulation and energy transport has been studied. FindingsIt has been found that a raise of the nanoadditives concentration intensifies the cooling of the heat-generating element, while a growth of the heat-generation frequency allows reducing the amplitude of the heater temperature. Originality/valueMathematical modeling of a pseudoplastic nanomaterial thermogravitational energy transport in an electronic cabinet with a periodic thermally generating unit, a heat-conducting substrate and isothermal cooling vertical surfaces to identify the possibility of intensifying heat removal from a heated surface.
Keywords: Pseudoplastic fluid; Nanofluid; Natural convection; Square enclosure; Periodic heat-generated solid element; Heat-conducting substrate